THE INFLUENCE OF THE PARIS CLIMATE AGREEMENT ON ENERGY AND ENVIRONMENTAL POLICY REFORM IN INDONESIA - Angelina Dwi Susanti; Friska Silaban; Lambok Febryan Aritonang; Yessi Tri Yosika Br Sitompul (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Climate change is a global challenge that is driving countries to reform their energy and environmental policies, including Indonesia. Before the Paris Climate Agreement was ratified in 2016, Indonesia's policies were sectoral, fragmented, and highly dependent on fossil energy, with minimal attention to reducing carbon emissions. This study aims to analyze the impact of the Paris Climate Agreement on energy and environmental policy changes in Indonesia. The research approach applied is descriptive qualitative with an online literature study method, using sources from scientific journals, books, government documents, and international reports. The research findings indicate that the Paris Climate Agreement acts as a key driver of national policy change towards low-carbon development. Indonesia began to implement new instruments such as Nationally Determined Contributions (NDC), carbon tax, Emissions Trading System (ETS), and set energy transition targets in the 2021-2030 RUPTL. In addition, environmental policies are emphasized through the integration of climate change issues in the RPJMN, RAN-GRK, forest moratorium, and the establishment of the Peat Restoration Agency. Despite significant progress, policy implementation still faces challenges in terms of coordination and resistance from various sectors.